1994
DOI: 10.1002/oti.6150010303
|View full text |Cite
|
Sign up to set email alerts
|

Menstrual management and intellectual disability: New perspectives

Abstract: Assessment and education

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Roughly half of our sample also needed help with their personal hygiene during menstruation (see also Rodgers 2006; Mason & Cunningham 2007) and their carers often reported that they found providing this aspect of care somewhat unpleasant, as well as rather intrusive (see also Carnaby & Cambridge 2002). Despite this, some women, although potentially able to cope, are never given the opportunity to learn how to manage their own menstrual care (Griffen et al . 1994; Grover 2002; Rodgers et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Roughly half of our sample also needed help with their personal hygiene during menstruation (see also Rodgers 2006; Mason & Cunningham 2007) and their carers often reported that they found providing this aspect of care somewhat unpleasant, as well as rather intrusive (see also Carnaby & Cambridge 2002). Despite this, some women, although potentially able to cope, are never given the opportunity to learn how to manage their own menstrual care (Griffen et al . 1994; Grover 2002; Rodgers et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…General occupational therapy textbooks such as those edited by Bumphrey (1995), Christiansen and Baum (1997) and Neistadt and Blesedell Crepeau (1998) do not refer to any of these issues. However, in the occupational therapy literature there are references to occupational therapists having a role with people with intellectual disability in areas such as ‘dental health’ (Cullen‐Erickson, 1994), ‘menstrual management’ (Griffin, Carlson, Taylor & Wilson, 1994), ‘personal health care’, ‘sexuality’ (Llewellyn, 1991b; p. 235), and ‘self care’ and ‘liaison with other organisations’ (Tannous, Lehmann‐Monck, Magoffin, Jackson & Llewellyn, 1999; p. 28).…”
Section: Introductionmentioning
confidence: 99%
“…Support workers can help people with ID to achieve positive results by using the right model. An intervention model to assist menstrual management was found to yield good results (Griffin et al. 1994).…”
Section: Resultsmentioning
confidence: 99%
“…Support workers can help people with ID to achieve positive results by using the right model. An intervention model to assist menstrual management was found to yield good results (Griffin et al 1994). A study of hospital experiences found that people with ID were given more fluid to drink and more assistance in getting out of bed if a support person was with them.…”
Section: Positive Experiences In Relation To Healthmentioning
confidence: 99%
See 1 more Smart Citation